Al-Ummi Dalam Al-Qur’an; Studi Tafsir Tematik Terhadap Literasi Nabi Muhammad - Muhammad (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
One of the mandatory nature of the prophet is intelligent. One sign of someone can be said to be intelligent when able to read-write. If the Prophet Muhammad was unable to read the writing, he lost one of his face traits. Scholars interpret the pronunciation of al-Ummi by not being able to read writing. When interpreted so can damage the prophetic reputation. This article discusses the intent of al-Ummi pronunciation in the Qur'an using qualitative method, using the Muá¸Å«'Ä« interpretation approach, which is to compile the pronunciation of al-Ummi in the Qur'an, then recite one the pronunciation. Historically, rebuilding history has passed through the events of the corner as they were in the current space and time. Sociology, analyzing the truth from a social standpoint. By knowing the social conditions Arab Jahiliyah became a strong source of the presence or absence of write writing at the time. The results of the study show that writing was already running during the Jahiliyyah. All of Muhammad's uncle was able to read writing. None of the relevant pronunciation of al-Ummi is interpreted as unable to read the writing, but al-Ummi's pronunciation in the Qur'an has a meaning of 1) Arabs. 2) People who have never listened to scripture readings.